1998
DOI: 10.1002/j.1551-8833.1998.tb08500.x
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne outbreaks of cryptosporidiosis

Abstract: A review of 35 outbreaks of cryptosporidiosis points to recommendations for prevention of waterborne outbreaks and uncovers a need for more adequate epidemiological data. Cryptosporidium parvum infection occurs worldwide in urban and rural populations, and waterborne outbreaks have been associated with consumption of contaminated drinking water and water during recreational activities. This article reviews the epidemiology and causes of waterborne outbreaks that have been reported in North America and the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 50 publications
2
94
0
5
Order By: Relevance
“…Most of the reported outbreaks associated with protozoan pathogens, namely Giardia and Cryptosporidium, occur through water (Craun et al, 1998;Barwick et al, 2000;Lee et al, 2002;Karanis et al, 2007a;Baldursson and Karanis, 2011). Here, we report the detection of Cryptosporidium after application of IFT as one conventional method and two molecular tools using the SSU rRNA gene for nested PCR and the SAM gene for LAMP assays.…”
Section: Discussionmentioning
confidence: 79%
“…Most of the reported outbreaks associated with protozoan pathogens, namely Giardia and Cryptosporidium, occur through water (Craun et al, 1998;Barwick et al, 2000;Lee et al, 2002;Karanis et al, 2007a;Baldursson and Karanis, 2011). Here, we report the detection of Cryptosporidium after application of IFT as one conventional method and two molecular tools using the SSU rRNA gene for nested PCR and the SAM gene for LAMP assays.…”
Section: Discussionmentioning
confidence: 79%
“…This notion was first raised independently by Craun and colleagues (262) and Hunter and Quigley (259), who reported that attack rates were significantly higher for outbreaks associated with groundwater than surface water consumption. They argued that people who use surface water sources were regularly exposed to small numbers of oocysts and thus did not experience many outbreaks, unless there was a major breakdown in treatment.…”
Section: Host Factors and Cryptosporidium Virulencementioning
confidence: 99%
“…Cryptosporidium is responsible for many waterborne outbreaks in the United States (4,19,34), the United Kingdom (4), and other countries (3). Although person-to-person contact and domestic animals are some of the possible sources of infection, exposure to and/or consumption of contaminated drinking water and the use of surface waters for recreational activities are among the most important routes of transmission of these parasites (8).…”
mentioning
confidence: 99%